Effects of Mutual Coupling and Noise Correlation on Downlink Coordinated Beamforming with Limited Feedback. (2nd June 2009) - Dong Dong, Yuhan Yuhan; Domizioli Domizioli, Carlo P. Carlo P.; Hughes Hughes, Brian L. Brian L.
Abstract : We consider the impact of receiver correlation, antenna coupling, matching, and noise on the performance of coordinated beamforming systems. We present a new coordinated beamforming technique for two receivers that is suitable for MIMO broadcast channels with signal and noise correlation at the receiver. We then apply this technique to the specific type of signal and noise correlation that occurs in the presence of receiver mutual coupling. Numerical results suggest that, even in the presence of strong coupling, most of the benefits of coordinated beamforming can be preserved by using appropriate matching networks and linear beamforming. Moreover, these benefits can be achieved even when feedback is limited.